Urgensi Ratifikasi Statuta Roma dan Implikasinya terhadap Efektivitas International Criminal Court dalam Penegakan Hukum HAM Internasional - Sagara Alam (Perkara : Jurnal Ilmu Hukum dan Politik, 2026)
The increasing occurrence of genocide, war crimes, crimes against humanity, and other serious human rights violations demonstrates the continuing need for an effective international legal mechanism capable of ensuring accountability beyond national jurisdictions. The International Criminal Court, established under the Rome Statute of the International Criminal Court, represents a permanent institution designed to prosecute individuals responsible for the most serious international crimes. However, the effectiveness of the Court remains highly dependent on state participation through ratification of the Rome Statute. This study aims to analyze the urgency of Rome Statute ratification and its implications for the ICC's effectiveness in enforcing international human rights law. The research employed a normative legal method using statute, conceptual, and comparative approaches. Data were collected through a literature review of international treaties, national regulations, scholarly publications, and institutional reports relevant to the subject. The findings indicate that wider ratification significantly strengthens the legitimacy, jurisdictional reach, and operational capacity of the ICC, particularly in areas such as investigation, arrest cooperation, evidence gathering, and enforcement of judicial decisions. For Indonesia, ratification may encourage harmonization of domestic law with international standards, improve accountability mechanisms for gross human rights violations, and enhance the country’s credibility in global legal diplomacy. This study contributes to the discourse on the relationship between state sovereignty and international accountability by demonstrating that ratification should be understood not as a loss of sovereignty, but as a commitment to responsible governance and justice. In conclusion, ratification of the Rome Statute constitutes a strategic legal step toward strengthening global human rights enforcement and promoting sustainable legal reform.